The development and mechanistic investigation of a palladium-catalyzed 1, 3-arylfluorination of chromenes. Issue 4 (9th February 2017) - Thornbury, Richard T.; Saini, Vaneet; Fernandes, Talita de A.; Santiago, Celine B.; Talbot, Eric P. A.; Sigman, Matthew S.; McKenna, Jeffrey M.; Toste, F. Dean
Abstract : A mild palladium-catalyzed ligand-controlled regioselective 1, 3-arylfluorination of 2[ H ]-chromenes has been developed. Abstract : A mild palladium-catalyzed ligand-controlled regioselective 1, 3-arylfluorination of 2[ H ]-chromenes has been developed. The products with a syn -1, 3 substitution pattern were obtained with high enantiomeric excess using a PyrOx ligand, wherein the utility of these pyranyl-fluorides was further demonstrated through their participation in a diastereoselective C–C bond forming reaction. Ligand dependent divergent formation of both the 1, 3- and 1, 2- alkene difunctionalization products was observed. The nature of this bifurcation was investigated through experimental studies in combination with computational and statistical analysis tools. Ultimately, the site selectivity was found to rely on ligand denticity and metal electrophilicity, the electronics of the boronic acid, and the donor ability of the directing group in the substrate.